2015
DOI: 10.1016/j.ijsolstr.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Composite behavior of concrete materials under high temperatures

Abstract: a b s t r a c tThis study examines the performance of concrete under elevated temperatures at the meso-scale level of observation where aggregate particles and the embedding hydrated cement paste form interacting continua. Decomposing concrete into these two constituents leads to mismatch of the thermal and hydraulic transport properties and hence to self-equilibrating internal stresses introducing progressive damage of the mechanical response behavior of concrete. Thereby the internal stresses are disregarded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 26 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…For example, the obtained results can be used to properly design FRP stiffeners applied to concrete structures that are prone to various damaging phenomena (see, e.g., [38]). It should be noted that the case of a thermal variation Δ (thermal variations can sensibly affect the mechanical behaviour of structural elements, as shown in [39,40]) acting on the beam (for the effect produced by thermal loads on concrete structures, see, e.g., [38]) can be studied as the loading case of two symmetric axial end forces by assuming…”
Section: Resultsmentioning
confidence: 99%
“…For example, the obtained results can be used to properly design FRP stiffeners applied to concrete structures that are prone to various damaging phenomena (see, e.g., [38]). It should be noted that the case of a thermal variation Δ (thermal variations can sensibly affect the mechanical behaviour of structural elements, as shown in [39,40]) acting on the beam (for the effect produced by thermal loads on concrete structures, see, e.g., [38]) can be studied as the loading case of two symmetric axial end forces by assuming…”
Section: Resultsmentioning
confidence: 99%
“…In the mesoscale model, concrete is assumed as a composite material with two periodically distributed mesoscale components, cement paste and aggregates, represented by multiphase hygroscopic and heat conducting rigid porous media partially saturated with liquid water, e.g. [4,8]. The detailed description of the assumptions adopted for developing the model is given in our previous work [17].…”
Section: The Mesoscale Modelmentioning
confidence: 99%
“…However concrete is not just a two-phase composite; it has been found that the presence of grains in the cement paste causes a thin layer of matrix material surrounding each inclusion to be more porous than the bulk of the surrounding cement paste matrix. This layer is named interfacial transition zone (ITZ) and has relevant effects on the properties of concrete, being likely to act as the "weak link in the chain" when compared to the bulk cement paste and the aggregate particles [15,16].…”
Section: Concrete As a Multiphase Materialsmentioning
confidence: 99%